Effect of a flood event on the dynamics of phytoplankton and biogeochemistry in a large temperate Australian lagoon - Perran L. M. Cook; Daryl P. Holland; Andrew R. Longmore (Limnology and Oceanography, 2010)
In episodically driven estuaries, nutrient delivery is typically confined to sporadic flow events, followed by intense biogeochemical recycling of nutrients. We document the response of a temperate lagoon system with episodic winter‐ or spring‐dominated catchment inflows (Gippsland Lakes, southeast Australia) to a flood event. High winter inflows resulted in high surface‐water concentrations of inorganic nitrogen (IN; NO 2 − + NO 3 − + NH 4 + ) relative to reactive phosphorus (RP) with an IN :RP ratio > 100. This resulted in a rapid diatom and dinoflagellate bloom, which collapsed as water column nutrients were exhausted. Increased carbon delivery to the sediment stimulated benthic respiration and depleted bottom‐water oxygen, which led to a large release of RP from the sediments, decreasing the IN :RP ratio in the bottom water to ~6. Strong stratification of the water column allowed the accumulation of RP in the bottom water over spring and into summer. Mixing of RP from the bottom water over summer triggered the development of a Nodularia spumigena Mertens bloom. As such, the nutrient supply for the Nodularia bloom was through a biogeochemical filter that strongly favored N 2 ‐fixing cyanobacterial blooms by reducing IN :RP ratios through a combination of sediment denitrification and release of stored phosphorus from within the sediment. These observations lead us to the paradoxical conclusion that high nitrogen loading over winter contributed to severe nitrogen limitation over summer, and highlight the importance of controlling both nitrogen and phosphorus loading to estuaries.